Detecting Load Resistance and Mutual Inductance in Series-Parallel Compensated Wireless Power Transfer System Based on Input-Side Measurement - Longzhao Sun; Mingui Sun; Dianguang Ma; Houjun Tang (International Journal of Antennas and Propagation)
In wireless power transfer (WPT) system, the variations in load resistance and mutual inductance influence the output voltage and output current, making the system deviate from its desirable operating condition; hence, it is essential to monitor load resistance and mutual inductance. Using input-side measurement to detect load resistance and mutual inductance has great advantages, because it does not need any direct measurements on the receiving side. Therefore, it can remove sensors on the receiving side and eliminate communication system feeding back the load measurements. This paper investigates load resistance and mutual inductance detection method in series-parallel compensated WPT system. By measuring input current and input voltage, the equation for calculating load resistance is deduced; when the operating frequency is lower than or equal to the receiving-side resonant frequency, the rigorous mathematical derivations prove that load resistance can be uniquely determined by using only one measurement of input current and input voltage. Furthermore, the analytical expressions for identifying load resistance and mutual inductance are deduced. Experiments are conducted to verify the proposed method.